Tinjauan Peraturan Pemerintah Nomor 78 Tahun 2015 dan Hukum Islam Tentang Pengupahan (Studi Kasus Saung Dolken Resort Bogor) - Dodi Yarli Rusli; Widiana Astuti Elimansyah (Jurnal Hukum Ekonomi Syariah, 2019)
This study aims to determine how the remuneration system is in accordance withgovernment regulations and in accordance with sharia law with a case study at SaungDolken Resort Syariah Bogor. The method used in this research is observation, interviewand literature study. The data used are primary data obtained directly from the speakers.The results showed that the wage system at Saung Dolken Resort Syariah only applied anumber of government regulations number 78 of 2015 concerning wages among them asfollows: a. Wage period is done on a monthly basis; b. Wages given in cash (cash); c.There has been no overtime salary received by employees, but replaced with additionalfood; d. Wages paid are always on time; e. There is no deduction from wages for everyemployee who is unable to attend as long as the reason is acceptable to the company; f.The division of working hours is divided once every 8 hours into 3 shifts; g. Employeesare given facilities if they are entrusted with work outside the company; h. Employeesreceive Idul Fitri and Idul Adha holiday allowances. While in terms of sharia law SaungDolken Resort Syariah has fulfilled all sharia maqashid, namely: a. Hifdz Ad-Din(Maintaining Religion); b. Hifdz An-Nafs (Nurturing the Soul); c. Hifdz Al'Aql(Preserving Intellect); d. Hifdz An-Nasb (Nurturing Heredity); e. Hifdz Al-Maal(Preserving Assets).